'Return to the source and fetch': The curator as Sankofa. Issue 1 (1st March 2017) - Burton, David
The Sankofa bird stands as an appropriate metaphor for student curators in schools. The Sankofa alludes to the saying, 'Return to the source and fetch'. This, essentially, is what student curators do when they engage the roles and tasks of mounting art exhibitions in schools. Art exhibitions comprise five task areas: theme development, exhibition design, exhibition installation, writing and publicity, and the event where the exhibit is presented to the public. In theme development, the student curators must reach back to the origins they discovered in their art. In exhibition design and installation, they must build bridges between abstract themes and ideal spaces for their art to be displayed. Through writing they extend their sources and bring (fetch) them to their audience. In the final step − the event − they come full circle and fetch what they have learned for the benefit of the whole community.